Cost‐effectiveness of the Collaborative Care to Preserve Performance in Cancer (COPE) trial tele‐rehabilitation interventions for patients with advanced cancers - Colleen F. Longacre; John A. Nyman; Sue L. Visscher; Bijan J. Borah; Andrea L. Cheville (Cancer Medicine)
Abstract Purpose The purpose of this analysis was to determine the cost‐effectiveness of a Collaborative Care Model (CCM)‐based, centralized telecare approach to delivering rehabilitation services to late‐stage cancer patients experiencing functional limitations. Methods Data for this analysis came from the Collaborative Care to Preserve Performance in Cancer (COPE) trial, a randomized control trial of 516 patients assigned to: (a) a control group (arm A), (b) tele‐rehabilitation (arm B), and (c) tele‐rehabilitation plus pharmacological pain management (arm C). Patient quality of life was measured using the EQ‐5D‐3L at baseline, 3‐month, and 6‐month follow‐up. Direct intervention costs were measured from the experience of the trial. Participants’ hospitalization data were obtained from their medical records, and costs associated with these encounters were estimated from unit cost data and hospital‐associated utilization information found in the literature. A secondary analysis of total utilization costs was conducted for the subset of COPE trial patients for whom comprehensive cost capture was possible. Results In the intervention‐only model, tele‐rehabilitation (arm B) was found to be the dominant strategy, with an incremental cost‐effectiveness ratio (ICER) of $15 494/QALY. At the $100 000 willingness‐to‐pay threshold, this tele‐rehabilitation was the cost‐effective strategy in 95.4% of simulations. It was found to be cost saving compared to enhanced usual care once the downstream hospitalization costs were taken into account. In the total cost analysis, total inpatient hospitalization costs were significantly lower in both tele‐rehabilitation (arm B) and tele‐rehabilitation plus pain management (arm C) compared to control (arm A), (P = .048). Conclusion The delivery of a CCM‐based, centralized tele‐rehabilitation intervention to patients with advanced stage cancer is highly cost‐effective. Clinicians and care teams working with this vulnerable population should consider incorporating such interventions into their patient care plans.